Are individuals a problem for British structural-functionalist anthropology? - Edward, Terence Rajivan (IJRDO - Journal of Social Science and Humanities Research, 2023)
In this paper, I consider the objection to British structural-functionalism that it is unable to deal with the significance of individuals. There are various ways in which individuals may pose a problem for it. I identify four ways, one of which is novel. This way is when someone does not appear to meet the official role requirements in an organization, which gives rise to the question of whether the anthropologist should posit an alternative structure of roles for the organization.